Odpowiedzi

2009-11-25T18:10:15+01:00
⅓x=3
x=3:⅓
x=3*3/1
x=9
-----------


3/5x = -5
x=-5:3/5
x=-5*5/3
x=-15/3
x=-5

------------

3/9 x = -4
x=-4:3/9
x=-4*9/3
x=-36/3
x=-12
2009-11-25T18:12:44+01:00
1
- x = 3 /*3
3

x=9

3
-x = -5 /*5
5
3x=-25 /:3
x=-25/3=8 i 1/3

3
- x = 4
4 -9
(3/-5)x=4 /*(-5)
3x=-20 /:3
x=-20/3=6 i 2/3

2009-11-25T18:44:32+01:00
1
- x = 3 /*3
3
x=9
1
- * 9= 3
3
3=3

⅗x = -5 /*5
15x=-25/15
x=⅗

3
-----x = 4
4 -9
-⅗x=4 / * 5
-3x=20 /:(-3)
x= - 6⅔

Mam nadzieję, że o to Ci chodziło;)